Physician perception regarding side-effect profile at the onset of antidepressant treatment: a survey of Israeli psychiatrists and primary care physicians. Issue 1 (December 2016) - Nitzan, Uri; Bekerman, Tal; Becker, Gideon; Lichtenberg, Pesach; Lev-Ran, Shaul; Walter, Garry; Maoz, Hagai; Bloch, Yuval
Abstract Background One of the major factors affecting treatment compliance and outcome in patients is the wide range of side effects (SEs) associated with antidepressants. In the present study, we aimed to assess the extent to which Israeli primary care (PC) physicians and psychiatrists discuss the SEs of selective serotonin reuptake inhibitors (SSRIs) with patients prior to the onset of treatment. Methods A cross-sectional questionnaire survey was conducted among PC physicians (N = 123) and psychiatrists (N = 105). Questionnaires were distributed using a mixed-modality design, combining a web survey and in-person delivery of questionnaires. Results A significant percentage of our respondents reported that they rarely discuss psychological (60 %) or severe (29 %) SEs of SSRIs. Nearly half (41 %) admitted to avoiding discussion of impact on suicidal ideation. Specialists were noted to discuss and evaluate SEs significantly more than residents, and Psychiatrists more than PC physicians. Specifically, psychiatrists more often discussed the possibility of sexual dysfunction (t (225) = 2.23;p < 0.05) and suicidal ideation (t (225) = 2.11;p < 0.05). Conclusions It seems that PC physicians and psychiatrists surveyed in this study do not share sufficient information regarding the SEs of SSRIs with their patients at the onset of treatment. In improving this practice, the integration of proper SE management into educational interventions has potential in enhancing compliance and improving expertise and level of care.